Preparation and Characterization of Ni-Doped TiO2 Materials for Photocurrent and Photocatalytic Applications - Ibram Ganesh; A. K. Gupta; P. P. Kumar; P. S. C. Sekhar; K. Radha; G. Padmanabham; G. Sundararajan (The Scientific World Journal)
Different amounts of Ni-doped TiO2 (Ni=0.1 to 10%) powders and thin films were prepared by following a conventional coprecipitation and sol-gel dip coating techniques, respectively, at 400 to 800°C, and were thoroughly characterized by means of XRD, FT-IR, FT-Raman, DRS, UV-visible, BET surface area, zeta potential, flat band potential, and photocurrent measurement techniques. Photocatalytic abilities of Ni-doped TiO2 powders were evaluated by means of methylene blue (MB) degradation reaction under simulated solar light. Characterization results suggest that as a dopant, Ni stabilizes TiO2 in the form of anatase phase, reduces its bandgap energy, and adjusts its flat band potentials such that this material can be employed for photoelectrochemical (PEC) oxidation of water reaction. The photocatalytic activity and photocurrent ability of TiO2 have been enhanced by doping of Ni in TiO2. The kinetic studies revealed that the MB degradation reaction follows the Langmuir-Hinshelwood first-order reaction relationship.